1996
DOI: 10.1080/09638189600000014
|View full text |Cite
|
Sign up to set email alerts
|

Audit risk and audit programmes: archival evidence from four Dutch audit firms

Abstract: The audit risk model has become an extremely important element in audit practice. The basic intuition behind the model is that changes in risk should affect the work of the auditor. However, little systematic empirical evidence has been published on the assessment of audit risk and its effect on audit work. This study, using documentation from actual audits and follow-up interviews, provides such evidence. Assessments of audit risk and audit programme details have been obtained from eight clients of four Dutch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 4 publications
0
20
0
1
Order By: Relevance
“…This result indicates that the risk assessment is contributed significantly toward an effective audit program. One supportive study by Quadackers, Mock and Maijoor (1996) assessed the relationship between audit risk and audit program details. The results indicated that there is material variation in audit risk factors between clients and among the audit risk factors per client.…”
Section: Y = α0+ β1x1+ β 2x2+ β 3x3+ Ementioning
confidence: 99%
See 1 more Smart Citation
“…This result indicates that the risk assessment is contributed significantly toward an effective audit program. One supportive study by Quadackers, Mock and Maijoor (1996) assessed the relationship between audit risk and audit program details. The results indicated that there is material variation in audit risk factors between clients and among the audit risk factors per client.…”
Section: Y = α0+ β1x1+ β 2x2+ β 3x3+ Ementioning
confidence: 99%
“…The finding revealed that the administrative level to which the head of the internal auditing department reports and the level of the organizational independence of the internal auditing staff were the main important factors that affect the judgments made by external auditors in planning audit programs. Quadackers, Mock and Maijoor (1996) assessed the relationship between audit risk-as a one component of internal control components-and audit program planning details. The results indicated that there is much variation in audit risk aspects between clients and among the audit risk aspects per client.…”
Section: Internal Control and Audit Program Effectivenessmentioning
confidence: 99%
“…Blay et al (2008) believe that the ARM as a conceptual model promotes a risk, focused approach for allocation of audit procedures. This model has become an extremely important element in auditing (Quadackers et al 1996). Additionally, the ARM, as a normative model in the professional standards assists auditors in the judgment processes about risk (Blay et al, 2008;Iranian Audit Procedure, 2000).…”
Section: Audit Risk Modelmentioning
confidence: 99%
“…Many prior studies (Dusenbury, Reimers & Wheeler, 2000;Messier & Austen, 2000;Ritchie & Khorwatt, 2007;Bloomfield, 1995;Quadackers, Mock & Maijoor, 1996;Quick, 2012) studied the functional relationship among the variables of the Audit Risk Model (ARM) or examined the dependencies between the entity's environment as it is reflected in the business risk and in the designed and implemented audit approach. However, most studies regarding the interrelations of audit risk components have been focused on ARM variables at the assertions level and they mainly examine the inherent and control risk as two different risk components.…”
Section: Introductionmentioning
confidence: 99%
“…In the European environment, Quadackers et al (1996) examined the variability in audit risk and audit programs using data from eight clients of four Dutch audit firms. This study reports substantial variation in audit risk factors both between audited entities and among the audit risk factors per entity.…”
Section: Introductionmentioning
confidence: 99%